The Effect of Non-Performing Loans and Loan to Deposit Ratio on Return On Assets in the Banking Industry - et. al., Niki Hadian, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of Non Performing Loans and Loan to Deposit Ratio partially and simultaneously on Return On Asset in bank sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The factors tested in this study are the Non-Performing Loan and the Loan to Deposit Ratio as independent variables, while Return on Assets as the dependent variable. The method used in this research is descriptive and verification methods. The population in this study were the bank sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period, totaling 43 companies. The sampling technique used was non-probability sampling with a purposive sampling method, so that the total sample size was 27 companies. While the data analysis used is multiple linear regression analysis at a significance level of 5%. The results showed that partially and simultaneously the Non Performing Loan and the Loan to Deposit Ratio had an effect on Return On Assets. The magnitude of the influence of the Non Performing Loans and the Loan to Deposit Ratio in giving the contribution of the influence on the Return on Assets is 64.19%.